Water quality improvements and ecological inertia: a basin-wide assessment of ecosystem recovery in the Yangtze River system (2005–2022) - Xingchen Zhao; Yunlin Zhang; Haoran Tang; Qingji Zhang; Chixiao Cui; Boqiang Qin (Ecological Indicators)
The Yangtze River Basin is Asia’s largest fluvial network and a critical socio‐ecological system, yet decades of rapid economic development have degraded its water quality and biodiversity. Since the 2000s, China has implemented extensive pollution‑control and restoration policies targeting both rivers and lakes. Here, we synthesize an 18‑year (2005–2022) multisource dataset—including monthly measurements of 24 water‑quality parameters at 1,014 river cross‑sections, chlorophyll‑a (Chla) concentrations, remote‑sensing of macrophyte cover, benthic invertebrate surveys across 99 lakes, and upper‑river fish‑catch data (1998–2022)—to assess recovery trajectories across the basin. This integrated analysis revealed that rivers exhibited rapid and uniform improvements in total nitrogen (TN), total phosphorus (TP), ammonia‑N (NH3‑N), and permanganate index of chemical oxygen demand (CODMn), with 95.4 % of sites achieving China’s Grade I–III water quality by 2022 (Grade I indicating optimal water quality), reflecting successful pollution control measures. However, lakes exhibited a delayed response, as ecosystem recovery lagged water quality improvements due to ecological hysteresis. Despite Yangtze-disconnected lakes achieved the steepest TN reductions (−0.0513 mg/L/year), but TP trends were negligible, while Chla increased (up to + 1.41 mg/L/year in isolated systems). Remote sensing and field surveys further indicated widespread macrophyte loss, with threefold greater in hydrologically than connected systems (slope =  −1.4058 vs. −0.4633 km2/year), and significant reductions in macroinvertebrate abundance and species richness between 2007-2009 and 2018. Our findings demonstrated the decoupling of physicochemical recovery and biological responses in lakes, likely driven by legacy nutrients in sediments, long hydraulic residence times, habitat fragmentation, and warming temperatures. While the recent fishing ban in the upper Yangtze River has contributed to a partial recovery of fish populations, ensuring long-term ecological restoration requires a meta-coupled human and natural system approach—one that integrates natural and human systems to achieve synergistic solutions for sustainable development. This study underscores the urgent need for targeted management strategies to mitigate internal nutrient loading, enhance biodiversity conservation, and improve the resilience of aquatic ecosystems in the face of ongoing environmental change.